Verapamil Induces Calcium Influx in the Trachea - Seham Mustafa; Abdulkareem Abdulraheem; Abdulhakeem Alsughayer (Elsevier, 2008)
Verapamil, a Ca2+entry blocker, can induce bronchorelaxation and bronchoconstriction. The mechanism of verapamil-induced bronchoconstriction is poorly understood. The present study determines the direct effect of verapamil on smooth muscle of isolated ovine airways and analyzes the mechanisms involved. Isolated tracheal strips were suspended in organ baths containing Krebs solution for isometric tension recording. Tissue responses to verapamil as assessed by basal tone were examined in the presence or absence of epithelium. The effects of verapamil on carbachol and cooling-induced contraction were also recorded. Measurement of unidirectional fluxes was carried out using 45Ca2+in the absence or presence of verapamil. Verapamil induced contractions of basal tracheal smooth muscle that were proportional to its concentrations. Removal of epithelium did not affect the verapamil contractile effect. Verapamil-induced contractions were abolished in Ca2+-free Krebs solution containing 2 mM EGTA. Verapamil increased the 45Ca2+influx into the tracheal smooth muscle. It caused relaxation of the muscle tone induced by carbachol or KCl, but it potentiated the effect of cooling-induced contraction. Verapamil induced Ca2+influx that may lead to bronchoconstriction. These results proved that verapamil may worsen bronchoconstriction; therefore verapamil should be used with caution in asthmatic individuals. Keywords:: airway smooth muscle, trachea, calcium antagonist, asthma, 45Ca2+